Teaching for transformative educational experience in a sport for development program. Issue 4 (18th May 2016) - Wright, Paul M.; Jacobs, Jenn M.; Ressler, James D.; Jung, Jinhong
Abstract : Despite the assumption that Sport for Development and Peace programs can foster social change, many fail to provide intentional educational experiences. This limits the attainment and sustainability of positive outcomes for participants and communities. The literature calls for such programs to use sport as an educational tool that shifts power to participants in a way that is responsive and respectful to the local context. In this article, we present findings from a program designed to promote youth development and social change through youth sport in a Central American nation. The teaching personal and social responsibility (TPSR) model provides the instructional framework for this program and local coach training was guided by the principles of critical pedagogy. Participants were eight youth sport coaches who became local trainers in the program. Data sources include interviews, observations and artifacts. Participants appeared to have meaningful educational experiences characterized by the following themes: reframing the coach's role; personal reflection; developing a critical perspective; and increasing feelings of agency. Findings indicate that in this program, TPSR was a relevant instructional framework that combined effectively with the principles of critical pedagogy to foster transformative learning among the participants.